Persfektif Guru dan Orang Tua Murid Terhadap Pembuatan Alat Permainan Anak di TK Bakuwu UPR - Wiyogo Wiyogo; Debora Debora; Harie Satiyadi Jaya; Vontas Alfenny Nahan; Sri Murwantini; Sukardi Sukardi; Ahmad Eko Suryanto; Marko Ayaki Lumbantobing; Ratna Pancawati; Muhammad Hudan Rahmat; Supriyadi Supriyadi; Agung Samudra; Galfri Siswandi; Nurul Huda; Jeremy Imanuel Segah (Jurnal Ilmiah Kanderang Tingang, 2023)
In the world of children, physical activities are a vital key to their development, and play becomes a crucial aspect in this process. Utilizing play equipment, children's learning and interaction can be facilitated. Through the Community Engagement initiative conducted by the Mechanical Engineering Education at Bakuwu Kindergarten, Universitas Palangka Raya (UPR), innovative principles are integrated into the creation of children's play equipment. The primary objective of this initiative is to gain insights from both teachers and parents regarding the produced play equipment. The research methodology employs a mixed-methods design, incorporating Pareto analysis. The results reveal that maintenance and upkeep of the play equipment constitute a predominant issue, contributing to 34% of the overall problems. It can be concluded that the maintenance of play equipment is a critical element in enhancing the efficiency and effectiveness of activities. Sustained development and improvement have long-term benefits for children, educators, and the community. Recommendations for enhancement encompass heightened awareness, regular maintenance, and the implementation of continuous improvement cycles, aligning with the Pareto analysis principles that emphasize addressing the most significant issues for optimal outcomes.